Karakteristik CEO Dan Kinerja Perusahaan Non-Keuangan Yang Teraftar Di Bursa Efek Indonesia - I Made Sudana; Elka Dwiputri (Forum Manajemen Indonesia (FMI), 2018)
The purpose from this research is to test the effect from CEO characteristics towards firm performance. CEO characteristics was proxied with founder CEO, ownership, tenure, and education. Firm performance was proxied with Tobin’s Q. The sample from this research are every non-financial firm that have been listed in Indonesian Stock Exchange from 2010 – 2015 period. The method from this research is purposive sampling with analysis technique model multiple linier regression. The result from this research showed that founder CEO, CEO ownership, CEO tenure have a positive significant effect towards firm’s performance or Tobin’s Q. Keywords : CEO Characteristics, Firm Performance